A systematic review of diagnostic criteria for psoriasis in adults and children: evidence from studies with a primary aim to develop or validate diagnostic criteria - Burden-Teh, E.; Phillips, R.C.; Thomas, K.S.; Ratib, S.; Grindlay, D.; Murphy, R. (Wiley, 2017)
Background: The diagnosis of psoriasis in adults and children is made clinically, for both patient management and the selection of participants in research. Diagnostic criteria provide a structure for clinical assessment, which in turn helps standardise patient recruitment into clinical trials and case definitions in observational studies. Objective: The aim of this systematic review was to identify and critically appraise the published studies to date that had a primary research aim to develop or validate diagnostic criteria for psoriasis. Method: A search of Ovid MEDLINE and Ovid Embase was conducted in October 2016. The primary objective was sensitivity and specificity of diagnostic criteria for psoriasis. Secondary objectives included diagnostic recommendations, applicability to children and study characteristics. Diagnostic accuracy studies were critically appraised for risk of bias using the QUADAS-2 tool. Results: Twenty-three studies met the inclusion criteria.None detailed clinical examination-based diagnostic criteria. The included criteria varied from genetic and molecular diagnostic models to skin imaging, histopathology, questionnaire-based, computer-aided and traditional Chinese medicine criteria. High sensitivity and specificity (>90%) were reported in many studies. However, the study authors often did not specify how criteria would be used clinically or in research. This review identified studies with varyingrisk of bias and due to each study developing separate criteria meta-analysis was not possible. Conclusion: Clinical examination-based diagnostic criteria are currently lacking for psoriasis. Future research could follow an international collaborative approach and employ high quality diagnostic accuracy study design. Existing and newly developed criteria require validation.